The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physrevx.4.011027
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Long-Lived High-Power Optical Waveguides in Air

Abstract: We demonstrate that femtosecond filaments can set up an extended and robust thermal waveguide structure in air with a lifetime of several milliseconds, making possible the very-long-range guiding and distant projection of high-energy laser pulses and high-average power beams. As a proof of principle, we demonstrate guiding of 110-mJ, 7-ns, 532-nm pulses with 90% throughput over ∼15 Rayleigh lengths in a 70-cm-long air waveguide generated by the long time-scale thermal relaxation of an array of femtosecond fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 35 publications
6
100
0
Order By: Relevance
“…In the limit of laser intensities approaching and exceeding 10 14 W/cm 2 , i.e. above the typical ionization threshold, local gas heating due to the re-scattering of hot electrons in laser-induced plasma filaments is well understood [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the limit of laser intensities approaching and exceeding 10 14 W/cm 2 , i.e. above the typical ionization threshold, local gas heating due to the re-scattering of hot electrons in laser-induced plasma filaments is well understood [14].…”
mentioning
confidence: 99%
“…Nonlinear change of refractive index gives rise to filamentation (recent reviews of this broad topic can be found in [1,2]), whereas spatially localized heating results in the formation of acoustic waves [3][4][5][6][7][8] and long-lived gas density perturbations [9][10][11]. Photo-acoustic vibrational Raman spectroscopy has been successfully utilized for chemical detection and trace analysis [12,13].…”
mentioning
confidence: 99%
“…Polynkin et al experimentally observed the generation of curved plasma channels in both air and water by applying femtosecond Airy beams [9,10] . An extended and robust thermal waveguide structure in air with a lifetime of several milliseconds can be formed with femtosecond filaments [11] , making possible the very-long-range guiding and distant projection of high-energy laser pulses and high average power beams.However, the propagation characteristics of high power pulsed lasers at the interfaces of different transparent materials are ignored, particularly those of femtosecond filament. The air-glass surface is now widely used for the imaging of the lateral distribution of a filament [12][13][14] ; however, the propagation characteristics are neglected.…”
mentioning
confidence: 99%
“…Polynkin et al experimentally observed the generation of curved plasma channels in both air and water by applying femtosecond Airy beams [9,10] . An extended and robust thermal waveguide structure in air with a lifetime of several milliseconds can be formed with femtosecond filaments [11] , making possible the very-long-range guiding and distant projection of high-energy laser pulses and high average power beams.…”
mentioning
confidence: 99%
“…Propagation over such long distances is a result of the dynamic balance between the focusing Kerr nonlinearity, diffraction, and plasma defocusing due to multiphoton absorption. A proper arrangement of plasma channels into arrays built of multiple filaments can lead to control [5] and efficient guiding of electromagnetic radiation in air [6]. Dielectric [7] and hollow-core metallic waveguide configurations [8,9] were predicted theoretically and demonstrated experimentally [10] to guide microwave radiation.…”
mentioning
confidence: 99%